Penerapan Algoritma Term Frequency-Inverse Document Frequency (TF-IDF) Untuk Fitur Pencarian Dokumen Standar Nasional Indonesia - Ani, Nur; Yosephine Sinaga, Desi; Junior, Nickolas; Doni Munggaran, Muhamad (Fakultas Teknik Universitas Muhammadiyah Bengkulu, 2023)
Information about the Indonesian National Standard (SNI) is already available on the Ministry of Industry's Pustand website and also the BSN website. The SNI search process that is less effective and must be done on different websites will make it difficult for users and business actors. Therefore, the SNI search website using keywords is a solution that will facilitate the SNI search process. SNI search with keywords where users enter the words to be searched on the website and with the TF-IDF algorithm the website will appear any SNI that matches the keyword. In its application, the keywords entered by users on the SNI search website will go through preprocessing first, namely tokenizing, filtering, then stamming, and the TF-IDF algorithm will combine two methods, namely the concept of the frequency of the appearance of terms in an SNI document and inverse back documents that have the same meaning from the keywords entered by users into the system. This application will make it easier for business actors who want to find out about SNI for the product to be produced so that when the product already exists, business actors only need to register the product to be standardized in accordance with the applicable SNI according to the product description.